Predicting content proficiency through disciplinary-literacy variables in English-medium writing. (April 2021) - Sánchez-Pérez, María del Mar
Abstract: The debate on the roles of language and literacy in the increasingly internationalised university contexts where disciplinary content is taught through the medium of English has been a matter of recent research concerns. Despite the limited focus on language and literacy in English-medium instruction (EMI) programmes, there is currently increasing recognition of the need for explicit awareness of subject-specific language and literacies to favour content learning. However, there is a paucity of empirical research that measures the impact of students' disciplinary language and literacy skills on content achievement in EMI contexts. To address this issue, this paper analyses the relationship between the use of disciplinary-literacy variables related to the genre and specialized-language features of the laboratory report at the levels of text structure, cohesion, grammar, and vocabulary, and students' content proficiency in English-medium writing in a Spanish undergraduate setting. Results show a positive relationship between the frequency of occurrence of certain disciplinary-literacy variables and students' content proficiency. In particular, moves, cohesive devices, technical words, and passive voice appear as significant indicators of content proficiency in English-medium laboratory report writing. These findings strengthen the need to provide students with subject-specific language and literacy support for successful academic development in EMI courses.